AB0964 Macrophage Activation Syndrome in Patients with Systemic Juvenile Idiopathic Arthritis: Applicability of the Diagnosis Criteria. (9th June 2015) - Boteanu, A.L.; Medina Quiñones, C.; Blazquez Cañamero, M.A.; Guillen Astete, C.A.; Borja Serratti, J.F.; Gámir Gámir, M.L.
Abstract : Background: Macrophage activation syndrome (MAS) is one of the most severe complications of the Systemic Juvenile Idiopathic Arthritis (sJIA), characterized by a stage of inflammation due to a massive secretion of cytokine. The MAS associated to sJIA is considered as a part of acquired hemophagocytic lymphohistiocytic syndrome (HLH). The macrophage hemophagocytosis in the BM biopsy provides the definitive diagnosis of this serious complication; however the clinical and analytical features can be very important for the diagnostic of MAS. Preliminary criteria for the diagnosis of MAS associated with sJIA, validated in 2014, showed better sensitivity and specificity than HLH-2004 criteria. Objectives: To investigate the clinical and laboratory features of 7 episodes of MAS associated to sJIA, comparing the HLH-2004 criteria with the MAS-sJIA criteria. Methods: We conducted in a single center study including demographic data, clinical and laboratory features as part of the diagnostic criteria, possible triggers, treatment and outcome. Activity of NK cells and the levels of IL-2 receptor were not available in all patients, so it was considered as diagnostic the presence of 4/5 or 3/5 HLH-2004 criteria as proposed by PRINTO/PRES in 2014 Results: 66.6% of patients were women, with an variable age at presentation, between 2 and 24 years. The fever was the most common clinical manifestation, like thrombocytopenia, elevated GOT and ferritin, present in 100% of MAS episodes. The frequency of HLH-2004 criteria: fever 100%; elevated ferritin in 100%; anemia 27%; thrombocytopenia 42%; leukopenia 57%, splenomegaly 57%, increased triglycerides or reduction fibrinogen in 42% of cases. In 2 episodes it has been met only 3 of 5 adapted HLH criteria, in 1 case 4 of 5 criteria and 5 of 5 criteria in 4 cases. The frequency of MAS- sJIA criteria: increased of ferritin, GOT and thrombocytopenia was saw in 100% of cases, decreased fibrinogen in 71% and 57% had leucopenia. Bleeding manifestations have occurred in 57% of episodes. CNS manifestation has been diagnosis in 42% of episodes, and 57% presented with hepatomegaly. The increase in GOT and thrombocytopenia were the most frequent manifestations in the MAS-sJIA Conclusions: The MAS can appear early or after several years of evolution of the sJIA. In our series, all patients met the criteria for diagnosis of SAM according to adapted HLH-2014 criteria (3/5 or 4/5 adapted) as well as the MAS-sJIA criteria, but with a lower number of HLH-2014 criteria. Similar as in the series published in 2014, our patients have had less cytopenias and hypofibrinogenaemia according HLH-2004, this leads to a lower number of criteria and a doubtful diagnosis. The frequency of cytopenia and decreased of the fibrinogen as HLH-2004 was lower probably because the values they consider. The degree of cytopenias required in HLH-2004 criteria can be probably observed in more advanced stages of the disease. The MAS is a serious complication with a high mortality, so suspicion and early diagnosis are very important for prognosis. References: Sergio Daví, et al. Performance of current guidlines for diagnosis of macrophage activation syndrome complicating systemic juvenile idiopathic arthritis. Arthritis & Rheumatology 2014; 66, 2871-2880. Disclosure of Interest: None declared